2020
DOI: 10.26434/chemrxiv.13237307.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoelectron Spectra of Gd2O2− and Non-Monotonic Photon-Energy Dependent Variations in Populations of Close-Lying Neutral States

Abstract: <p>Photoelectron spectra of Gd<sub>2</sub>O<sub>2</sub><sup>−</sup> obtained with photon energies from 2.033 eV to 3.495 eV exhibit numerous close-lying neutral states with photon-energy-dependent relative intensities. Transitions to states falling within the electron binding energy window of 0.9 and 1.6 eV are attributed to one- or two-electron transitions to the ground and low-lying excited neutral states. An additional, manifold of electronic states observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The approach used here follows from our previous experience working with such systems as well as studies reported by other groups. 46,47,51,[69][70][71][72][73][74][75] 3 Results…”
Section: Methodsmentioning
confidence: 99%
“…The approach used here follows from our previous experience working with such systems as well as studies reported by other groups. 46,47,51,[69][70][71][72][73][74][75] 3 Results…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, over the last few years we have employed NIO analysis in studies of complicated photoelectron spectra of transition metal and lanthanide containing clusters. 20,21,[23][24][25]83,84 In We note that the remainder of this discussion focuses on electron detachment; analogous expressions can be derived for electron attachment processes.…”
Section: Introductionmentioning
confidence: 99%